Ellmann's Joyce, The Biography of a Masterpiece and its Maker: The Letter between Literature and Cinema. - Nadel, Ira; Chattopadhyay, Arka; Holman, Matthew (Journal of Modern Literature)
What motivated Richard Ellmann to write his biography of James Joyce, long established as a masterwork of twentieth century biography, exceeding in importance such stellar texts as Leon Edel's Henry James: A Life or George D. Painter's Marcel Proust? Zachary Leader explains why in his archive-centered biography of Ellmann the man and his Joyce book, providing new details and perspectives. But in documenting Ellmann's methods and discoveries, Leader hesitates to analyze several pitfalls of the text and the individual, while objecting to the role of critical theory in biographical writing. Sigi Jöttkandt's book The Nabokov Effect (2024) has implications for the Lacanian letter's traversal between literature and cinema. The book presents a new reading of Lacan's idea of the sinthome as a splitting of the subject and how it illuminates the way Nabokov subverts linear time and death by dialecticizing the semiotic systems of literature and cinema. I link Jöttkandt's reading of the letter in Vladimir Nabokov with Jacques Lacan's idea of "lituraterre" via a Nabokov trope, analyzed by Jöttkandt. I further extend her psychoanalytic approach by connecting the letter's trajectory between literature and cinema with Lacan's point that literature moves out of itself in its turn to "lituraterre." Frank O'Hara's New York School and Mid-Century Mannerism draws on artistic vocabularies of the High Renaissance, the Pindaric, and Mannerist period styles to offer a new way of reading the coterie culture, gestural performativity, and stylized aesthetics of the New York School, especially as they relate to Abstract Expressionism and neoclassical dance. Ladkin uses attentive close readings to highlight how Frank O'Hara, as the linchpin of the movement, articulated the excesses of the earlier Mannerist period by situating him within queer lineages from late Renaissance statuary to icons of postwar Hollywood.